Semiformalidad de la mediana y pequeña empresa (MIPYME) en Costa Rica y su relación con la competitividad y el desarrollo - Brenes Bonilla, Lizette (2012)
Half-formality of small and medium enterprises (MSMEs) in Costa Rica and its relation to the competitiveness and development. When studying the business dynamics of a country it is common to refer to two dissimilar situations: the formal and the informal businesses. However, there are companies that operate at different levels of formality or informality, and may be considered semi-formal. This analysis examines the semiformal condition of micro, small and businesses and their relationship to structure, competitiveness and development in Costa Rica. They are considered semi-formal firms with municipal license if they do not comply with other requirements. In Costa Rica, each local government has territorial jurisdiction over smaller geographic areas called “cantones”. Using multivariate statistics, we examined the relationship between the density of firms with municipal license and variables such as the Cantonal Competitiveness Index (CCI), the Human Development Index (HDI), the formal business density, reflected in the number of employers registered for the economically active population (EAP), the density of population and geographic area of the county. We found that in Costa Rica there are approximately three municipal permits (“patents”) by each employer enrolled in the national health insurance system (CCSS), which indicates that the semiformal bussiness is a business reality that deserves further analysis. There is a direct relationship between the density of patents and business owners, and competitiveness variables and cantonal development. Thus, there are counties where conditions favor the development of business initiatives, both formal and semiformal.KEY WORDSSMEs, semi-business, municipal licenses, employers, Human Development Index, Cantonal Competitiveness Index.